Connected Reading: A Framework for Understanding How Adolescents Encounter, Evaluate, and Engage With Texts in the Digital Age. Issue 2 (2nd August 2019) - Turner, Kristen Hawley; Hicks, Troy; Zucker, Lauren
Abstract: Since the emergence of the World Wide Web and e‐reading devices in the late 1990s and early 2000s, reading research has focused on issues of website credibility, search and navigation strategies, and the ability to comprehend text on‐screen as compared with in print. What has been missing, however, are data about the specific texts that adolescents are reading in these digital spaces, what devices they prefer, and the strategies that they employ. Drawing from survey data ( N = 804) and interviews ( n = 23) with participants in grades 7–12 from 12 suburban, urban, and rural schools across the United States, the authors sought to explore what, where, and how adolescents read digitally. The authors propose a new framework of connected reading, a model of print and digital reading comprehension that conceptualizes readers' interactions with digital texts through encountering (the ways in which readers seek or receive digital texts), evaluating (the ways in which readers make judgments about the usefulness of digital texts), and engaging (the ways in which readers interact with and share digital texts). In light of the findings, the authors argue that it is imperative to reframe discussions about how adolescents are taught to comprehend and interact with a variety of digital texts (e.g., webpages, e‐books, multimedia, social media).